Energy Efficient with Trust and Qos-Aware Optimal Multipath Routing Protocol Based on Elephant Herding Optimization for Iot Based Wireless Sensor Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
RPs (Routing Protocols) fail to consider node statuses like a node’s lifetime or congestions in networks in during transmissions. Node’s lifetime plays an important role as it needs sufficient energy to route or transmit information. However, QoS (Quality of Services) can improve network lifetimes specically in selections of multi-paths in routing information. This work proposes an energy efficient and optimal QoS aware multi-path routing protocol based on EHO (Elephant Herding Optimization) algorithm and trust called EHO-ETQRP for IoT (Internet of Things) based WSNs (Wireless Sensor Networks). This work’s objective function targets QoS parameters of trust and energy. The proposed protocol identified an optimal path for routing by computing costs involving congestion and lifetimes of nodes. The protocol is evaluated for its suitability where it produces satisfactory results.